Business Plan: Prakash Eco-power Forming A Strategic Alliance with A Foreign Manufacturer To Explore The New Business Opportunity at Hand, Utilizing The Current Resources of The Parent Company, and A Study on The Supply Chain Strategies and Issues. - Garg, Shwetang (2011)
This is a guide plan for the company and its executives to follow a growth strategy for the Prakash group, bringing in new products that are better and have a huge potential. This also outlines the various activities that need to be undertaken in the future for better profits and larger market share.